Coupled Aerodynamic–Hydrodynamic Analysis of Spar-Type Floating Foundations with Normal and Lightweight Concrete for Offshore Wind Energy in Colombia - Jose Calderón; Andrés Guzmán; William Gómez (Journal of Marine Science and Engineering)
Foundations for offshore wind turbines come in various types, with spar-type floating foundations being the most promising for different depths. This research analyzed the hydrodynamic–mechanical response of a 5 MW spar-type floating foundation under conditions typical of the Colombian Caribbean following the DNV standard. Two types of concrete were evaluated through numerical modeling: one with normal density (2400 kg/m3) and another with lightweight density (1900 kg/m3). Based on the hydrodynamic and structural dynamic response, it was concluded that the variation in concrete density only affected pitch rotation, with better performance observed in the lightweight concrete, achieving maximum rotations of 10°. The coupled model between QBlade and Aqwa was validated by code-to-code comparisons with QBlade’s fully coupled system with its ocean module. This study contributes to offshore engineering in Colombia by providing a detailed methodology for developing a coupled simulation, serving as a reference for both academia and industry amid the ongoing and projected wind energy development initiatives in the country.